(untitled) (Journal of economic and management development research, 2026)
Against the backdrop of the in-depth integration of culture and tourism, cultural and creative products of scenic areas (hereinafter referred to as “scenic cultural and creative products”) have become an important vehicle for inheriting regional culture and enhancing the added value of scenic destinations. However, the market for scenic cultural and creative products has been frequently troubled by counterfeit and imitation practices. In particular, the phenomenon whereby tourists purchase genuine products, reproduce them, and then sell the imitations at low prices through e-commerce platforms has seriously infringed upon the intellectual property rights of original creators, disrupted market order, and constrained the healthy development of the scenic cultural and creative industry. Taking this phenomenon as the central object of study, this paper reviews the current state of scenic cultural and creative product development and intellectual property protection, analyzes the formation mechanism and multiple harms of tourists’ counterfeit selling behavior, and, in light of typical cases, explores the deficiencies of the current intellectual property protection system in addressing this issue. Finally, it proposes targeted solutions from multiple dimensions, including rights holders, regulatory authorities, e-commerce platforms, and consumers, with the aim of providing theoretical references and practical guidance for improving the intellectual property protection mechanism for scenic cultural and creative products and promoting the high-quality development of the culture and tourism industry.